THE IMPACT OF THE DIGITAL ECONOMY ON ACCOUNTING - S.F. Turaeva (Scholar Express Journals, 2022)
Currently, accounting activities are in a phase of gradual development and introduction of new digital technologies. Thanks to the automation of accounting processes, most companies try to optimize all contractual activities. The digitalization of the economy creates opportunities for the creation of a national accounting system, which collects indicators characterizing the state of internal socio-economic processes of the company. The article examines the impact of digitalization on accounting, emphasizes its popularity with the use of blockchain technology and the advantages of its application.
Keywords: Optimization; trend; digital economy; accounting